Гастропротекторная эффективность гепатопротекторов у крыс с токсическим гепатитом = Gastroprotective effects of hepatoprotectors in toxic hepatite rats - Petrenko, A. A.; Levitsky, A. P. (Journal of Education, Health and Sport, 2016)
Petrenko А. A., Levitsky A. P. Гастропротекторная эффективность гепатопротекторов у крыс с токсическим гепатитом = Gastroprotective effects of hepatoprotectors in toxic hepatite rats. Journal of Education, Health and Sport. 2016;6(6):177-184. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55174 http://ojs.ukw.edu.pl/index.php/johs/article/view/3568 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. УДК 616.33+392.092 ГАСТРОПРОТЕКТОРНАЯ ЭФФЕКТИВНОСТЬ ГЕПАТОПРОТЕКТОРОВ У КРЫС С ТОКСИЧЕСКИМ ГЕПАТИТОМ А. А. Петренко1, А. П. Левицкий2 1Коммунальное учереждение «Одесская областная клиническая больница» 2ГУ «Институт стоматологии НАМН Украины» (г. Одесса, Украина) e-mail: flavan@mail.ru При токсическом гепатите, вызываемом гидразин сульфатом, в слизистой желудка крыс развивается воспаление, которое предупреждает введение гепатопротекторов (квертулин, леквин или лекасил). Ключевые слова: гепатит, гастрит, гепатопротекторы. GASTROPROTECTIVE EFFECTS OF HEPATOPROTECTORS IN TOXIC HEPATITE RATS А. A. Petrenko1, A. P. Levitsky2 1Municipal Institution «Odessa Regional Clinical Hospital» 2SE«The Institute of Stomatology of the National acаdemie of medical science of Ukraine» (Odessa, Ukraine) e-mail: flavan@mail.ru Summary Aim: To determine of gastroprotective effects of new hepatoprotectors in toxic hepatite rats. Materials and Methods: The toxic hepatite was reproduced by hydrazine sulphate (50 mg/kg in one day, three days). Quertulyne (quercethin + inulin + calcium citrate), lekvin (lecithin + quercethin + inulin + calcium citrate) and lecasil (lecithin + flavolignan silybum+ calcium citrate) were used as hepatoprotects in doses 300 mg/kg during 14 days. Hepatite was established by levels of hepatic elastase and alkaline phosphatase, and serum MDA and serum elastase. The inflammation in gastric mucosa (gastritis) was established by levels inflammation markers: MDA content and elastase activity. Results: Levels inflammation markers increased into gastric mucosa of toxic Hepatite rats. The introduction of the hepatoprotectors prevented of gastric mucosa inflammation, but the urease activity no was changed. Conclusion: Hepatogenic gastritis may be consepnenced by of the action of liver acute-phase proteins. Keywords: hepatite, gastritis, hepatoprotectore.